Canada : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
Canada's 2005 Article IV Consultation highlights that it has benefited from a strong institutional framework and continuing structural reforms. Inflation targeting and structural reforms have yielded an enviable macroeconomic performance, including the fastest growth rate and the strongest budget position in the G-7. The outlook for the economy is broadly favorable, but external developments are creating uncertainties. The Bank of Canada appears to have room to maintain a patient and measured approach to withdrawing stimulus.